Affine Translation Surfaces in the Isotropic 3-Space - Aydin, Muhittin Evren; Ergut, Mahmut (Int Electronic Journal Geometry, 2017)
In this paper, we describe (linear) Weingarten affine translation surfaces of first kind in the isotropic 3-space. In addition, we obtain such surfaces that satisfy certain equations in terms of the position vector and the Laplace operator.
Keywords: Isotropic space; affine translation surface; Weingarten surface